The handbook of humanistic psychology : theory, research, and practice - Schneider, Kirk J.; Pierson, J. Fraser; Bugental, James F. T. (Thousand Oaks, California : SAGE Publications, Inc., 2015)
The Second Edition of the cutting edge work, The Handbook of Humanistic Psychology, by Kirk J. Schneider, J. Fraser Pierson and James F. T. Bugental, represents the very latest scholarship in the field of humanistic psychology and psychotherapy. Set against trends inclined toward psychological standardization and medicalization, the handbook offers a rich tapestry of reflection by the leading person-centered scholars of our time. Their range in topics is far-reaching-from the historical, theoretical and methodological, to the spiritual, psychotherapeutic and multicultural. The new edition of this widely adopted and highly praised work has been thoroughly updated in accordance with the most current knowledge, and includes thirteen new chapters and sections, as well as contributions from twenty-three additional authors to extend the humanistic legacy to the emerging generation of students, scholars, and practitioners
pt. I Historical overview: The roots and genealogy of humanistic psychology / Donald Moss ; Humanistic psychology at the crossroads / Eugene I. Taylor and Frederick Martin ; Humanistic psychology and women : a critical-historical perspective / Ilene A. Serlin and Eleanor Criswell ; Humanistic psychology and multiculturalism : history, current status, and advancements / Louis Hoffman, Heatherlyn Cleare-Hoffman, and Theopia Jackson -- pt. II Humanistic theory: The search for the psyche : a human science perspective / Amedeo Giorgi ; Rediscovering awe : a new front in humanistic psychology, psychotherapy, and society / Kirk J. Schneider ; The person as moral agent / Thomas Szasz ; The self and humanistic psychology / Donald E. Polkinghorne ; Toward a sustainable myth of self : an existential response to the postmodern condition / Louis Hoffman, Sharon Stewart, Denise M. Warren, and Lisa Meek ; Humanistic psychology and ecology / Marc Pilisuk and Melanie Joy ; Humanistic psychology and peace / Marc Pilisuk ; Two noble insurgencies : creativity and humanistic psychology / Mike Arons and Ruth Richards ; Becoming authentic : an existential-humanistic approach to reading literature / Thomas Greening ; Fellini, Fred, and Ginger : imagology and the postmodern world / Edward Mendelowitz ; Humanistic neuropsychology : the implications of neurophenomenology for psychology / Brent Dean Robbins and Susan Gordon ; Humanistic eldercare : toward a new conceptual framework for aging / Nader Shabahangi ; Toward a humanistic-multicultural model of development / Eugene M. DeRobertis ; Humanistic psychology in dialogue with cognitive science and technological culture / Christopher M. Aanstoos -- pt. III. Humanistic methodology: Humanistic psychology and the qualitative research tradition / Frederick J. Wertz ; An introduction to phenomenological research in psychology : historical, conceptual, and methodological foundations / Scott D. Churchill and Frederick J. Wertz ; The grounded theory method and humanistic psychology / David L. Rennie and Rinat Nissim ; Heuristic research : design and methodology / Clark Moustakas ; Narrative research and humanism / Ruthellen Josselson and Amia Lieblich ; Research methodology in humanistic psychology in light of postmodernity / Stanley Krippner ; Hermeneutic single-case efficacy design : an overview / Robert Elliott -- pt. IV Humanistic applications to practice: Introduction : the renewal of humanism in psychotherapy--a roundtable discussion / Kirk J. Schneider and Alfried A. Langle ; The renewal of humanism in European Psychotherapy : developments and applications / Alfried A. Langle and Jurgen Kriz ; Humanism and multiculturalism : an evolutionary alliance / Lillian Comas-Diaz ; The renewal of humanism in psychoanalytic therapy / Robert D. Stolorow ; Humanism as a common factor in psychotherapy / Bruce E. Wampold ; Toward a common focus in psychotherapy research / David N. Elkins ; Humanistic psychology and contextual behavioral perspectives / Steven C. Hayes ; The renewal of humanism in psychotherapy : summary and conclusion / Kirk J. Schneider and Alfried A. Langle ; Frames, attitudes, and skills of an existential-humanistic psychotherapist / Bob Edelstein ; Therapy as an I-Thou encounter / Maurice Friedman ; The person of the therapist : one therapist's journey to relationship / Barry L. Duncan ; Existential cross-cultural counseling : the courage to be an existential counselor / Clemmont E. Vontress and Lawrence R. Epp ; Treating madness without hospitals : Soteria and its successors / Loren Mosher ; Awe comes shaking out of the bones / E. Mark Stern ; If you are ready to undergo these awe-full moments, then have an experiential session / Alvin R. Mahrer ; Constructivist approaches to therapy / Larry M. Leitner and Franz R. Epting ; A humanistic perspective on bereavement / Myrtle Heery ; Existential analysis and humanistic psychotherapy / John Rowan ; A reply to John Rowan / Ernesto Spinelli ; Humanistic psychology's transformative role in a threatened world / Maureen O'Hara ; Humanistic-experiential therapies in the era of managed care / Jeanne C. Watson and Arthur C. Bohart ; An existential-integrative approach to experiential liberation / Kirk J. Schneider -- pt. V Humanistic applications to broader settings: Collaborative exploration as an approach to personality assessment / Constance T. Fischer ; Cultivating psychotherapist artistry : model existential-humanistic training programs / J. Fraser Pierson, Orah T. Krug, Jeffrey G. Sharp, and Troy Piwowarski ; Humanistic psychology, mind-body medicine, and whole-person health care / Eleanor Criswell and Ilene A. Serlin ; Romantic love as a path : tensions between erotic desire and security needs / G. Kenneth Bradford ; Beyond religion : toward a humanistic spirituality / David N. Elkins ; Authenticity, conventionality, and angst : existential and transpersonal perspectives / Roger Walsh ; A reply to Roger Walsh / Kirk J. Schneider ; Humanistic psychology and social action / Donaldrian L. Rice ; Humanistic psychology in the workplace / Alfonso Montuori and Ronald Purser -- pt. VI Epilogue : looking back and looking forward: Closing statements / Kirk J. Schneider, J. Fraser Pierson, and James F.T. Bugental
Includes bibliographical references and index
online resource; title from PDF title page (ProQuest Ebook Central, viewed November 19, 2020)
Master record variable field(s) change: 050
Keywords: Humanistic psychology; PSYCHOLOGY -- Reference; Humanistic psychology; Electronic books